Dichloromethyl[1-(2-pyridyl)ethanone benzoylhydrazonato]tin(IV) - Affan, M.A; Shamsuddin, M.B; Yusof, M. S M (Blackwell Munksgaard, 2004)
The chelate Sn - O - C - N - N - C - C - N fragment, together with the substituent methyl C atom, in the title complex, [SnCl2(CH 3)(C14H12N3O)], is planar, allowing the tridentate O,N,N-donor atoms and the methyl ligand C atom to occupy the equatorial positions in an octahedral environment. The geometry of the Sn atom is distorted octahedral, with a Cl - Sn - Cl axial bond angle of 172.02 (3)Â°.